Anatoly Nilolaevich Кеyеr - BARGPO, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The articles deals with the 80th birthday of Honoured Scientist, Head of the Information-Methodological Section of St. Petersburg Occupational-Rehabilitative Centre for the Disabled, Professor Кеyеr A. N.